HADIS-HADIS TENTANG HIJAMAH : Telaah Pemahaman Hadis dan Relevansi Terhadap Kesehatan - Rohman (Jurusan Ilmu Hadis Fakultas Ushuluddin, Dakwah dan Adab UIN Sultan Maulana Hasanuddin Banten, 2022)
Hadith is a source of Islamic teachings that has an important position besides the Qur'an. Apart from functioning to clarify the verses of the Qur'an which are still general in nature, hadith also function as a source of information related to the teachings of the Prophet Muhammad SAW in the form of sunnah or customs that cannot be found in the verses of the Qur'an. In the context of health, it is found that there are hadiths related to the treatment methods of the Prophet Muhammad SAW which are practiced to this day, one of which is quite popular among Muslims is the method of treatment using techniques.hijama (cupping). Hadiths related to hijamah (cupping) can be found in several hadith books and all hadiths regarding hijamah (cupping) show the correspondence between one hadith and another hadith. So it can be concluded that the hadith about hijamah (cupping) is an authentic hadith